Communication strategy in coping with COVID-19: Experience report - Paiva, Jamile de Souza Pacheco; Rocha, Moniky Keuly Marcelo; Freire, Camila Peixoto de Lima; Feitosa, Anna Karuza Nogueira; Brandão, Bruno Ferreira; Alves, Jamille Soares Moreira; Belo, Natália Paes; Reis, Virginia Angelica Silveira; Silva, Rivânio Paulino da; Herzer, Thais Lobo (Seven Editora, 2023)
Communication is an essential instrument for the effectiveness of health practices, enabling the dissemination of information, experiences and the development of improvement and innovation strategies. This study aimed to report the experience of creating a communication management committee, as a strategy to maintain dialogue with family members in coping with COVID-19. This was a descriptive study of experience report, contemplating the description of the phases of the process of implementation of the strategy developed at the General Hospital Dr. Waldemar Alcântara (HGWA), managed by the Institute of Health and Hospital Management (ISGH) in Fortaleza, Ceará. The results obtained with the strategy were positive, both for the family members as well as for the patient. It is concluded that in addition to communication, it was possible to strengthen the transition of care, through the multidisciplinary record in the medical record and allow greater integration with the sectors, sensitization of professionals, and approximation of family members. DOI:https://doi.org/10.56238/emerrelcovid19-069